Cancer core length from targeted biopsy: an index of prostate cancer volume and pathological stage. (24th February 2019) - Simopoulos, Demetrios N.; Sisk, Anthony E.; Priester, Alan; Felker, Ely R.; Kwan, Lorna; Delfin, Merdie K.; Reiter, Robert E.; Marks, Leonard S.
Abstract : Objective: To study the relationship of maximum cancer core length (MCCL), on targeted biopsy (TB) of magnetic resonance imaging (MRI)‐visible index lesions, to volume of that tumour found at radical prostatectomy (RP). Patients and Methods: In all, 205 men undergoing fusion biopsy and RP were divided into two groups: 136 in whom the MCCL came from an index MRI‐visible lesion (TB) and 69 in whom MCCL came from a non‐targeted lesion (non‐targeted biopsy [NTB]). MRI was 3‐T multi‐parametric and biopsy was via MRI‐ultrasonography fusion. Results: In the TB group, MCCL correlated with volume of clinically significant index tumours (ρ = 0.44–0.60, P  < 0.01). The correlation was similar for first and repeat biopsy and for transition and peripheral zone lesions (ρ = 0.42–0.49, P  < 0.01). No correlations were found in the NTB group. TB MCCL (6–10 and >10 mm) and MRI lesion diameter (>20 mm) were independently associated with tumour volume. TB MCCLs >10 mm and Gleason scores >7 were each associated with pathological T3 disease (odds ratios 5.73 and 5.04, respectively), but MRI lesion diameter lesion was not. Conclusions: MCCL on a TB from an MRI‐visible lesion is an independent predictor of both cancer volume and pathological stage. This relationship does not exist for MCCL from a NTB core. Quantifying CCL on MRI‐TBs may have a value, not previously described, to risk‐stratify patients with prostate cancer before treatment.